KONFIGURASI RUANG KAWASAN PASAR HONGKONG DENGAN METODE SPACE SYNTAX - Uray Najwa Amalia; Bontor Jumaylinda Br Gultom; Affrilyno Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
This research is based on the phenomenon of the importance of urban service spaces for tourist areas and users in them. For example, the Singkawang City service area that has been developed and is crowded with visitors is the Hongkong Market area. This area is a tourist destination in the form of a row of commercial and culinary buildings along Jl. Budi Utomo, Jl. Setia Budi and the surrounding streets. Seeing the importance of the city service space for tourist areas, it is necessary to optimize the city service space which is relatively easy for the community to cross. The purpose of this study is to find out the potential and problems of user distribution as seen from the spatial configuration of the Hongkong Market area. This study uses the space syntax to determine the achievement of the movement of visitors in the circulation space. The data analyzed by the space syntax first with the depthmapX 0.50. The results obtained from the space syntax are in the form of circulation data to determine the tendency of people to choose routes using axial map and visual graph mapping (VGA). The calculation analysis technique uses connectivity, integration, choice, step depth and intelligibility. Analysis space syntax is in the form of proposed findings by adding culinary facilities to the Traditional Area alley and Jalan Muslimin Ismail.